'Short' Double-Balloon Enteroscope for Endoscopic Retrograde Cholangiopancreatography in Patients with a Surgically Altered Upper Gastrointestinal Tract. (2011) - Cho, S; Kamalaporn, P; Kandel, G; Kortan, P; Marcon, N; May, G
Abstract : BACKGROUND: Endoscopic retrograde cholangiopancreatography (ERCP) remains a challenge for endoscopists in patients with surgically altered anatomy of the upper gastrointestinal tract. Double-balloon enteroscopes (DBEs) have revolutionized the ability to access the small bowel. The indication for its therapeutic use is expanding to include ERCP for patients who have undergone small bowel reconstruction. Most of the published experiences in DBE-assisted ERCP have used conventional double-balloon enteroscopes that are 200 cm in length, which do not permit use of the standard ERCP accessories. The authors report their experience with DBE-assisted ERCP using a 'short' DBE in patients with surgically altered anatomy. METHODS: A retrospective review of patients with previous small bowel reconstruction who underwent ERCP with a 'short' DBE at the Centre for Therapeutic Endoscopy and Endoscopic Oncology (Toronto, Ontario) between February 2007 and November 2008 was performed. RESULTS: A total of 20 patients (10 men) with a mean age of 57.9 years (range 26 to 85 years) underwent 29 sessions of ERCP with a DBE. Six patients underwent Billroth II gastroenterostomy, seven patients Roux-en-Y hepaticojejunostomy, five patients Roux-en-Y gastrojejunostomy, one patient Roux-en-Y esophagojejunostomy and one patient a Whipple's operation with choledochojejunostomy. Some patients (n=12 [60%]) underwent previous attempts at ERCP in which the papilla of Vater or bilioenteric anastomosis could not be reached with either a duodenoscope or pediatric colonoscope. All procedures were performed with a commercially available DBE (working length 152 cm, distal end diameter 9.4 mm, channel diameter 2.8 mm). The procedures were performed under conscious sedation with intravenous midazolam, fentanyl and diazepam, except in one patient in whom general anesthesia was administered. Either the papilla of Vater or bilioenteric anastomosis was reached in 25 of 29 cases (86.2%) in a mean duration of 20.8 min (range 5 min to 82 min). Bile duct cannulation was successful in 24 of 25 cases in which the papilla or bilioenteric anastomosis was reached. Therapeutic interventions were successful in 15 patients (24 procedures) including sphincterotomy (n=7), stone extraction (n=9), biliary dilation (n=8), stent placement (n=9) and stent removal (n=8). The mean total duration of the procedures was 70.7 min (range 30 min to 117 min). There were no procedure-related complications. CONCLUSION: DBEs enable successful diagnostic and therapeutic ERCP in patients with a surgically altered anatomy of the upper gastrointestinal tract. It is a safe, feasible and less invasive therapeutic option in this group of patients. Standard 'long' DBEs have limitations of long working length and the need for modified ERCP accessories. 'Short' DBEs are equally as effective in reaching the target limb as standard 'long' DBEs, and overcomes some limitations of long DBEs to result in high success rates for endoscopic therapy.